Rule of Law and Rule of Ethic in Law Enforcement in Indonesia - Toule, Elsa Rina Maya (SASI, 2022)
Introduction: Ethics cannot be separated from law. In law enforcement, ethics and law work together to realize legal ideals. Law enforcement officials need ethical considerations so that the law enforcement process can run well. Ethics acts as an important guide to ensuring proper and appropriate behavior in legal practice. Areas of coverage of ethical standards include sacred values, solidarity, theoretical, power, economics, and skills.Purposes of the Research: The purpose of this study is to provide a description of the importance of ethics in law enforcement in Indonesia. In addition to the substance of the law, law enforcement officers are a very influential factor. The law can be implemented properly if law enforcement officers have good ethical basic values.Methods of the Research: The research method used is normative juridical, which is research that examines documents, namely by using various primary, secondary and tertiary legal materials such as laws and regulations, court decisions, legal theory, and can be in the form of opinions of scholars. The approach in this research is the concept and law approach.Results of the Research: The results of the study indicate that the legal profession is a profession that is full of ethical values, because it deals with various humanitarian interests from society in general through actions and decisions taken. In reality, law enforcement officers actually make the law not upright to achieve its goals. Thus, legal knowledge alone is not enough, the ethics of law enforcement officers becomes a reference for upholding the law properly in society.